O contexto de trabalho dos(as) servidores(as) da Universidade Federal de Santa Maria: proposta de ações para promoção da saúde e qualidade de vida no trabalho (QVT) - Pieve, Denise Ribeiro da Fonseca da (2023)
Work is one of the factors that can contribute to health promotion, as it is through it that subjects can acquire better living conditions. In addition, it is in the work environment that the worker spends most of his time. Considering the importance of public servants' participation in assessing the work context and building actions to promote health and Quality of Life at Work (QWL), the main objective of this dissertation was to analyze the work context of the UFSM servants with regard to health in order to study the QWL to propose actions aimed at a healthy work environment. Considering the servants' perception of their work environment, in addition to being a democratic process, is a QWL action from a preventive perspective. This is essential for promoting the health of these workers. For this, descriptive research was carried out with a quantitative and qualitative approach with an applied purpose. The research worked with a sample of 425 civil servants from a population of 3,522 educational servants and administrative technicians. Data were collected through a questionnaire answered voluntarily, in virtual mode and analyzed using descriptive statistics and content analysis. As a result of this work, it was observed the existence of critical factors to be faced for a better perception of QWL, mainly in relation to the work organization factor (the pace of work is accelerated; the demand for results is present and the tasks are fulfilled with time pressure). Based on these data, it was possible to construct a proposal for health promotion and QWL actions for the institution's servants. In addition, the research provided subsidies that can improve the existing work and also direct the planning and organization of actions developed at UFSM towards a healthy work environment, reducing obstacles to health promotion and resulting in the improvement of services provided to employees (the) citizens.